The Field Skills' Development through Teaching Environmental Interactions in High School: Draa-Tafilalet Region, Morocco - Mariam Akdim; Anouar Alami; Sabah Selmaoui; Aboubakr Sabiri; Hamid Akdim (MDPI AG, 2022)
The study apprehends the educational impacts of fieldwork in earth sciences teaching at high school. We assess its role in students' skills improvement, based on a trip to Ait Idir (Ait Sedrate) in southeastern Morocco. The adopted approach consists of comparing skills acquired by a group of 26 high school students before and after the fieldwork. The area was chosen based on its scientific relevance, mainly in terms of morphologic diversity and accessibility. The students were engaged in the fieldwork on 4 December 2021 after doing a classroom course on introductive geology, granulometry, and sands' morphoscopy. In the field, students were asked to observe and discuss chosen landforms and deposits that may facilitate their skills development. Several technic tools were used such as maps, satellite images, and other geotechnical and mechanical tools. The results show the important positive impact of the fieldwork in teaching earth sciences at high school. It offered observable elements that students enjoy describing and discussing. The students engage their critical thinking to assess and discuss the landscape structure, the geomorphic forms, and their genetic processes and perceive the importance of the scale concepts for example. The post-test confirms that 53% of the students gave the right answers to asked general questions on topography, deposits, landforms, contextualization, and human-nature interactions for example. A total of 75% of asked questions were correctly answered by students concerning the site location, its physical framework, and its sedimentologic impacts. The research results are important in terms of soft skills development, and regarding their scientific, didactic, and cognitive impacts.